Transient and locally restricted expression of the ros1 protooncogene during mouse development. - Sonnenberg, E (1991)
The ros1 gene was detected originally by virtue of its transforming potential; the cDNA of the human protooncogene was isolated from a tumor cell line expressing the gene ectopically. It encodes a receptor-type tyrosine specific protein kinase which is closely related to sevenless in Drosophila. Here we report the novel and remarkable in vivo expression pattern of c-ros1, which was determined in the mouse. By a combination of RNase protection and in situ hybridization, we find transient c-ros1 expression during development in the kidney, intestine and lung, coinciding with major morphogenetic and differentiation events in these organs. This temporally restricted nature of expression is unusual for tyrosine kinase receptors and suggests a role for ros1 during development. Furthermore, in kidney development c-ros1 transcripts are confined to subgroups of ureter cells known to be involved directly in inductive interactions between ureter epithelium and metanephric mesenchyme. Thus, this study implicates for the first time a tyrosine kinase receptor in mesenchymal epithelial interactions and suggests a molecular basis for these important inductive events in development.